The use of english swear words among chinese youths / Tian Huey Ni Fanny - Tian, Fanny Huey Ni (2014)
This study was aimed to investigate the usage of English swear words among Chinese youths as well as to compare the use of swear words between male and female youths. The framework of this study is made up of the works of Battistella (2005), Lakoff (1995) and Talbot (1998). The participants consisted of seventy four (74) students studying at a private secondary school in the state of Selangor. Instrumentation used for the survey included a 26 item questionnaire and semi-structured interviews with focus groups. Two categories of focus groups consisted of randomly selected participants from the same sample and English language teachers from the school of the participants. Permission to conduct the study was obtained from the school principal, teachers and participants. The analysis was based on Battistella (2005) for taboo language and Lakoff (1995) and Talbot (1998) for gender and language. The results showed that the most common swear words among Chinese male and female youths belong to the obscenity category. The study infers that anger was the main reason for swearing among both genders. However, male youths also cited that the need of self- identity and the use of swear words were also due to peer influence. Female youths, on the other hand, indicated that swearing was linked to emotions. The study also found that male youths tend to swear more in the same gender group while female youths tend to swear more in mixed gender group. The study also found that the presence of different genders in the environment largely influences male language choice but not the female speakers. In conclusion, it is hoped that the findings of this study will be able to shed some light on the choice use of language among Chinese youths.